Physiological responses to interval training sessions at velocities asociated with VO2max - Rozenek, R.; Funato, K.; Kubo, J.; Hoshikawa, M. (The Journal of Strength and Conditioning Research, 2007)
Previous research has indicated that short-duration, high-intensity work intervals performed at velocities associated with maximal oxygen uptake (vVO2max) combined with active recovery intervals may be effective in eliciting improvements in endurance performance. This study was designed to characterize selected physiological responses to short-duration (<=60 seconds) interval work performed at velocities corresponding to 100% of vVO2max. Twelve men participated in 3 randomized trials consisting of treadmill running using work (W)/recovery (R) intervals of 15 seconds W/15 seconds R (15/15); 30 seconds W/15 seconds R (30/15); and 60 seconds W/15 seconds R (60/15). Work intervals were performed at 100% of vVO2max, whereas R intervals were performed at 50% of vVO2max. A fourth trial consisting of continuous work (C) at 100% of vVO2max was also performed. All subjects completed the 15/15 and 30/15 trials; however, only 5 of the 12 completed the 60/15 trial. The percentage of VO2max (mean +/- SD) during 15/15 (71.6 +/- 4.2%) was significantly lower (p <= 0.05) than the percentages during 30/15 (84.6 +/- 4.0%), 60/15 (89.2 +/- 4.2%), or C (87.9 +/- 5.0%). Similar results were found for heart rate and perceived exertion. Blood lactate concentrations following exercise were significantly lower (p <= 0.05) in 15/15 (7.3 +/- 2.4 mmol[middle dot]L-1) than in the other trials. No significant differences (p > 0.05) existed among 30/15 (11.5 +/- 1.8 mmol/L), 60/15 (12.5 +/- 1.8 mmol/L) or C (12.1 +/- 1.8 mmol/L). High intensity, short-duration 2:1 W/R intervals appear to produce responses that may benefit both aerobic and anaerobic energy system development. A 4:1 W/R ratio may be an upper limit for individuals in the initial phases of interval training.